Keeping Yoursel Well: Self-Care in Promoting Counselors' Psychological Well-Being - Voon, Siok Ping (PERKAMA International, 2018)
Helping profession like counselor is characteristically attuned to caring for other. Yet, it costs to care for others. Helping others can be painful for the helper. Thus, having a sense of psychological well-being is crucial to maintaining a healthy personal and professional self. Creating a sustainable balance between caring for clients and caring for ourselveshas become an important concept in promoting counselor psychological well-being. However, the concept of self-care has not received enough attention in Malaysia. This paper identifies the hazards of the counseling profession and self-care as ethical imperative, highlights the importance of self-care in promoting counselor’s psychological well-being and discusses the future direction of its research and practice among counselors in Malaysia.